Penyelenggaran Jaminan Produk Halal dalam Memberikan Perlindungan Hukum Konsumen Muslim di Indonesia Pasca Putusan Mahkamah Konstitusi Nomor 91/PUU-XVIII/2020 - Febriyanti, Wiwin Dwi Ratna (Journal of Law, Society, and Islamic Civilization, 2023)
Eating halal food and drinks is a must for Muslims, so it is very important to be able to identify whether the products to be consumed are halal. Indonesia, as a country with a majority Muslim population, must continue to strive to improve its security as a form of legal protection for its people. In this research, we will discuss the urgency of implementing halal product guarantees and implementing halal certification for products circulating in Indonesian society. To answer this problem, the researcher used legal research methods, using a statutory approach and a conceptual approach. As a form of legal protection for Muslim communities, it is very important for the State to create a legal basis regarding halal certification in various laws and regulations, but with the existence of the Law on Cipta Kerja, many legal bases have been removed, changed or replaced so that it becomes more systematic. Implementation of the application of halal certification, self-declaration applies, where business actors, especially small and micro, can apply self declare as long as the raw materials and product manufacturing processes do not contain materials and processes that are no risk or not halal.